Wybrane zagadnienia występujące w sporach między konsumentami a bankami na kanwie umów o kredyty waloryzowane do walut obcych - Smoliński, Tomasz; Tyska, Magdalena (Kortowski Przegląd Prawniczy, 2022)
This article deals with important and current issues concerning mainly settlements of an invalid loan agreement or a loan agreement indexed with a foreign currency exchange rate, considering its exchange rate provisions as illegal in contracts with consumers and therefore ineffective. The aim of the article was only to initiate a discussion on indexed contracts, which were concluded with consumers on a scale unprecedented in other legal systems. The current number of claims submitted by borrowers against banks, despite their wide scale, constitutes only a fraction of all concluded loan agreements indexed to foreign currencies and potentially invalid or non-binding to consumers in terms of indexation clauses. Therefore, the article focuses on showing possible decisions of common courts. The reasons for which the contract may be considered completely invalid as well as the reasons for which the obligation relationship under the indexed contract may still be maintained are presented. The consequences of potential legal and tax rulings as to the settlement of an invalid loan agreement, or the amount obtained due to unjustified overpayments on the loan while maintaining the agreement in force, disregarding indexation, were also indicated.